2008
DOI: 10.1002/cncr.23992
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 and pharmacokinetic study of concurrent carboplatin and irinotecan in subjects aged 1 to 21 years with refractory solid tumors

Abstract: Objective Spleen tyrosine kinase (Syk) has been identified as an important modulator of immune signaling in B cells and cells bearing Fcγ‐activating receptors. R788, a prodrug of active metabolite R406, has been shown to be an inhibitor of Syk kinase, active in a variety of in vitro and in vivo models, suggesting potential activity in the treatment of rheumatoid arthritis (RA). Methods We enrolled 189 patients with active RA despite methotrexate therapy in a 3‐month, multicenter, ascending‐dose, double‐blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…D and F, columns, mean value of VEGF and CD31 and MMP-2 and MMP-9 expressions; errors bars, 95% CI; n.s., not significant; *, P < 0.05; **, P < 0.01;***, P < 0.001. disease stabilization (29), or no objective response (6), as in treatment with the camptothecin analogue topotecan (5). When given in combination with other agents, camptothecin analogs have shown efficacy in preclinical neuroblastoma models (30,31) and in phase I clinical trials (32,33). More interestingly, an orally available formulation of irinotecan, in combination with temozolomide, led to partial response in a small number of relapsed high-risk neuroblastoma patients and was well tolerated (34).…”
Section: Discussionmentioning
confidence: 99%
“…D and F, columns, mean value of VEGF and CD31 and MMP-2 and MMP-9 expressions; errors bars, 95% CI; n.s., not significant; *, P < 0.05; **, P < 0.01;***, P < 0.001. disease stabilization (29), or no objective response (6), as in treatment with the camptothecin analogue topotecan (5). When given in combination with other agents, camptothecin analogs have shown efficacy in preclinical neuroblastoma models (30,31) and in phase I clinical trials (32,33). More interestingly, an orally available formulation of irinotecan, in combination with temozolomide, led to partial response in a small number of relapsed high-risk neuroblastoma patients and was well tolerated (34).…”
Section: Discussionmentioning
confidence: 99%
“…Irinotecan‐related toxicity appeared to be acceptable in our study and previous phase I and II trials, where toxicity was generally well documented, and neutropenia and diarrhea were consistently reported as the most common toxicities, with only occasional cases of grade 3–4 toxicity …”
Section: Discussionmentioning
confidence: 99%
“…observed more responses to topotecan in patients with intermediate‐risk (IR) histology compared to those with high‐risk (HR) histology . So far, limited information on irinotecan for relapsed WT is available from preclinical and phase I/II studies, showing some antitumor activity, but no randomized studies have been performed . Researchers from the Children's Oncology Group are evaluating irinotecan combined with other chemotherapeutic agents in upfront treatment for metastatic diffuse anaplastic WT, a diagnosis with a poor prognosis .…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity was manageable, particularly when amifostine was used to reduce myelosuppression. Levy et al have recently reported a pediatric Phase I study of single-dose carboplatin and dx5x2 intravenous irinotecan [70]. Prominent toxicities were diarrhea/abdominal pain and myelosuppression, despite the planned use of filgrastim.…”
Section: Irinotecan + Platinum Agentsmentioning
confidence: 97%